Construction and validation of an instrument for event-related sterility of processed healthcare products - Vanessa Aparecida Vilas-Boas; Louise Assumpção Rondini; Thamiris Cavazzani Vegro Czempik; Ada Helena Melo Lorenzetti; Kazuko Uchikawa Graziano; Ariane Polidoro Dini (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To construct and validate an instrument to assess events related to maintaining the sterility of processed healthcare products. Methods: This methodological study developed the instrument through analysis by a panel of experts, focusing on the integrity of commonly used packaging: spunbond-meltblown-spunbond and medical-grade paper. The instrument was analyzed using the Content Validity Index and Content Validity Ratio (≥ 0.80) and modified Kappa (≥ 0.74). The instrument underwent pre-testing. Results: Six experienced professionals participated in the expert panel. After two rounds, the final version of the instrument contained five dimensions. In the pre-test, 30 nursing professionals participated, of whom 86.67% considered the instrument good, and 90% found it understandable. Conclusion: The construction and validation followed literature recommendations. The instrument is available, aiding in the safe use of processed healthcare products.